The innovation potential of bulk nanostructured materials - Valiev, Ruslan Z.; Zehetbauer, Michael J.; Estrin, Yuri; Höppel, Heinz Werner; Ivanisenko, Yulia; Hahn, Horst; Wilde, Gerhard; Roven, Hans J.; Sauvage, Xavier; Langdon, Terence G. (Advanced Engineering Materials, 2007)
The innovation potential is high for bulk nanostructured materials (BNM) produced by methods of severe plastic deformation and accordingly this report focuses on very recent developments demonstrating the potential of using BNM for advanced and functional applications in engineering and medicine.
Created from Fastlane, Scopus look-up